Analisis Faktor-Faktor Yang Mempengaruhi Pengalokasian Belanja Modal Pada Pemerintah Kabupaten Dan Kota Di Sumatera Barat Periode 2017-2019 - Yois Nelsari Malau; Ade Rina Hutahaean; Lucia Fransiska Tampubolon (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study is aimed at analyzing the influence of PAD, DAU, DAK and DBH on Capital Expenditures in West Sumatra. The total population and sample are 19 districts/cities with a research period of 3 (three) years, namely 2017 to 2019 and using a saturated sampling technique as a sampling method. Testing the data hypothesis using the classical assumption test and the coefficient of determination obtained by Adjusted R Square of 0.612 means that what PAD, DAU, DAK and DBH can explain to regional expenditures is 61.2%, and other factors not examined in the study this is 38.8%. The results of the discussion partially prove that PAD, DAU and DBH do not affect capital expenditures. However, DAK influences capital expenditures. Simultaneously PAD, DAU, DAK and DBH influence capital expenditure. Keywords : Regional Original Revenue, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, and Capital Expenditure